Peran guru IPS sebagai pendidik dan pengajar dalam meningkatkan sikap sosial dan tanggung jawab sosial siswa SMP - Edy Surahman; M. Mukminan (Harmoni Sosial: Jurnal Pendidikan IPS, 2017)
Penelitian ini bertujuan untuk: (1) mengetahui peran guru IPS sebagai pendidik dan pengajar di SMP Negeri 1 Pangkajene Sidrap; (2) mengetahui sikap sosial siswa SMP Negeri 1 Pangkajene Sidrap; (3) mengetahui tanggung jawab sosial siswa SMP Negeri 1 Pangkajene Sidrap; (4) mengetahui pengaruh peran guru IPS sebagai pendidik dan pengajar dalam meningkatkan sikap sosial siswa SMP Negeri 1 Pangkajene Sidrap; dan (5) mengetahui pengaruh peran guru IPS sebagai pendidik dan pengajar dalam meningkatkan tanggung jawab sosial siswa SMP Negeri 1 Pangkajene Sidrap. Analisis data penelitian ini menggunakan analisis regresi linear sederhana. Hasil penelitian menunjukkan: (1) sumbangan peran guru IPS sebagai pendidik dan pengajar sebesar 62,7%; (2) sumbangan sikap sosial siswa SMP Negeri 1 Pangkajene Sidrap sebesar 67,1%; (3) sumbangan tanggung jawab sosial siswa SMP Negeri 1 Pangkajene Sidrap sebesar 62,7%; (4) peran guru IPS sebagai pendidik dan pengajar terbukti berpengaruh positif dalam meningkatkan sikap sosial siswa; (5) peran guru IPS sebagai pendidik dan pengajar juga terbukti berpengaruh positif dalam meningkatkan tanggung jawab sosial siswa. Jadi dapat disimpulkan bahwa guru mata pelajaran IPS sebagai pendidik dan pengajar dapat mempengaruhi sikap sosial dan tanggung jawab sosial siswa dengan cara guru memberikan contoh langsung dan spontan pada siswa.Kata Kunci: peran guru, sikap sosial, tanggung jawab sosial, guru IPS THE ROLE OF SOCIAL STUDIES TEACHER AS AN EDUCATOR AND TEACHERS ON INCRASE THE SOCIAL ATTITUDE AND SOCIAL RESPONSIBILITY STUDENTS OF SMPAbstractThis study aims to: (1) determine the role of Social Studies teachers as educators and teachers in SMP Negeri 1 Pangkajene Sidrap; (2) determine social attitudes of students of SMP Negeri 1 Pangkajene Sidrap; (3) determine the social responsibility of students of SMP Negeri 1 Pangkajene Sidrap; (4) the effect of the role of Social Studies teachers as educators and teachers on the social attitudes of students SMP Negeri 1 Pangkajene Sidrap; and (5) the effect of the role of Social Studies teachers as educators and teachers to social responsibility of students SMP Negeri 1 Pangkajene Sidrap. The data analysis used simple regression analysis. Finding of this research shown (1) contribution the role of Social Studies teachers as educators and teachers is 62.7%; (2) contribution social attitudes of students SMP Negeri 1 Pangkajene Sidrap is 67.1%; (3) contribution social responsibility of students SMP Negeri 1 Pangkajene Sidrap is 62.7%; (4) the role of Social Studies teachers as educators and teachers proved to be a positive influence on increase students' social attitude; (5) the role of Social Studies teachers as educators and teachers also proved a positive influence on increase the students' social responsibility. So it can be concluded that the Social Studies teachers as educators and teachers can influence social attitudes and social responsibility of students with the teacher gives examples for students directly and spontaneously.Keywords: role of teachers, social attitude, and social responsibility, social studies teachers